STUDENTS TEACHERS’ VIEWPOINTS ON THE IMPLEMENTATION OF BRIDGING COURSE FOR IMMERSION PROGRAM - Deni Sapta Nugraha (Jurnal Bebasan, 2014)
This study investigated the practice of bridging course for immersion program at the graduate program, State University of Malang by looking closely at how the student teacher viewed the course concerning four related aspects; factors affecting successful learning English, material used during the program, expected English skills mastery, and lecturer’s qualification and strategies. Eight respondents from chemistry RSBI class were given an open questionnaire to get the data. This study reported that the students viewed the course was useful for them to prepare their speaking proficiency before implementing an immersion program in their own schools. Also, they argued that being proficient in speaking skill is the most important if compared with the other skills. They optimist about the results because the instructor was considered has good qualification and strategies to teach English. Nonetheless, there have been some factors that impede their learning English such as lack of the books, limited time for learning English, and less confident to speak English.